Effect of acupuncture on post-operative pain in Lumbar surgery - Hamza, Fatine (2020)
According to the Heidelberg model of TCM, we designed clinical randomized single blinded controlled trial to investigate if acupuncture can be a useful therapeutic option in post-operative pain in lumbar surgery. To achieve this goal 30 patients were randomly assigned to two groups: Group one: intervention group received acupuncture in three points (KI10), (BL40) and (SP6). Control group received Sham acupuncture in three points that doesn't belong to any meridian. Both groups received the acupuncture by leopard spot technique and the treatment was given 24h after lumbar surgery for LDD and LSS. The pain assessment was evaluated by subjective measurement (VAS)and objective by measuring the angle of the hip in (lasegue Test) before and after acupuncture. Our results showed a significant decrease in the pain on VAS and a significant increase in angle measurement between before and after the acupuncture in both groups and no difference between the two groups. Our results confirmed that acupuncture can be used as a post-operative pain analgesic; it also proved the efficiency of the points choice. However, the therapeutic effect found in the control group is not unusual and can be explained by several theories: a.leopard spot technique that has a systemic effect on the qi and xue of the body.b.Sham points had common dermatomes with true acupoints. In conclusion: Acupuncture showed to be an effective way of treatment in postoperative pain in lumbar surgery for LDD and LSS, It can be used effectively as an adjunct to conventional analgesia in surgery departments.